The Role of Brand Image Mediation on Motivation and Word-of-Mouth on Study Decisions: A Study of Indonesian Diaspora Students in South Korea - Moh Musafak; Tin Agustina Karnawati; Teguh Widodo (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2025)
The growing interest in international education and bold learning, particularly among the diaspora community, raises questions about the factors influencing learning decisions. This study examines the role of brand image as a mediator between motivation, word of mouth, and study decisions in Indonesian diaspora students enrolled in the Online Korean language program. The quantitative approach was used through an online survey involving 59 Indonesian students at Cyber Hankuk University of Foreign Studies (CUFS), South Korea. The data were analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. The study results show that motivation positively affects brand image and indirectly influences learning decisions through brand image. In contrast, word of mouth has a significant but negative direct influence on learning decisions and does not significantly affect brand image. These findings confirm that brand image plays an important role as a mediator and needs to be managed strategically to optimize motivation into registration decisions, especially in the face of negative word-of-mouth narratives. This research provides practical implications for universities in designing more effective branding and communication strategies to attract diaspora learners in the context of bold education.